2011
DOI: 10.1590/s1807-59322011001200014
|View full text |Cite
|
Sign up to set email alerts
|

Total inspiratory and expiratory impedance in patients with severe chronic obstructive pulmonary disease

Abstract: OBJECTIVES:Several studies have confirmed the high potential of the forced oscillation technique for the assessment of respiratory modifications related to chronic obstructive pulmonary disease. However, most of these studies did not employ within-breath analyses of the respiratory system. The aim of this study is to analyze respiratory impedance alterations in different phases of the respiratory cycle of chronic obstructive pulmonary disease patients and to evaluate their clinical use.METHODS:39 individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 41 publications
(85 reference statements)
3
22
0
Order By: Relevance
“…Note the smaller difference between inspiration and expiration in the normal subject ( Figure 5A) and the higher values of expiratory impedance in the COPD patient ( Figure 5B). The parameters used to interpret raw single-frequency FOT data depend slightly on the research group (Dellacà et al 2004;Johnson et al 2005;Dellacà et al 2010;Silva et al, 2011). In general, Zrs and its components (Rrs, Xrs) are considered as the mean values during inspiration (Zi, Ri, Xi) and expiration (Ze, Re, Xe), the difference between Xi and the mean Xe (Xrs) has been used as an index of expiratory flow limitation (Dellacà et al 2004).…”
Section: Mono-frequencymentioning
confidence: 99%
See 3 more Smart Citations
“…Note the smaller difference between inspiration and expiration in the normal subject ( Figure 5A) and the higher values of expiratory impedance in the COPD patient ( Figure 5B). The parameters used to interpret raw single-frequency FOT data depend slightly on the research group (Dellacà et al 2004;Johnson et al 2005;Dellacà et al 2010;Silva et al, 2011). In general, Zrs and its components (Rrs, Xrs) are considered as the mean values during inspiration (Zi, Ri, Xi) and expiration (Ze, Re, Xe), the difference between Xi and the mean Xe (Xrs) has been used as an index of expiratory flow limitation (Dellacà et al 2004).…”
Section: Mono-frequencymentioning
confidence: 99%
“…In general, Zrs and its components (Rrs, Xrs) are considered as the mean values during inspiration (Zi, Ri, Xi) and expiration (Ze, Re, Xe), the difference between Xi and the mean Xe (Xrs) has been used as an index of expiratory flow limitation (Dellacà et al 2004). In previous studies from our group (Silva et al, 2011), the mechanical alterations during different phases of the respiratory cycle were characterized using the following parameters:…”
Section: Mono-frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…Silva et al (55) found that, in patients with severe COPD, respiratory alterations can be identified by increased respiratory system impedance, which is more evident in the expiratory phase. Their results seem to confirm the potential of within-breath analysis of respiratory impedance for the assessment of COPD-related respiratory alterations.…”
Section: Copdmentioning
confidence: 99%